Frequency and antifungal susceptibility of Candida spp. (other than C. albicans) isolated from patients admitted to critical care units of a third-level hospital in northern Peru - Vásquez-Zamora, Keila Guillermina (2020)
Objective: To determine the frequency and antifungal susceptibility of Candida spp. (other than C. albicans) isolated from samples of patients admitted to critical care units of a third-level hospital in northern Peru. Materials and methods: A cross-sectional study was conducted between February 2018 and May 2019 in 232 samples of patients admitted to critical care units of the Hospital Regional Lambayeque (HRL). Candida spp. (other than C. albicans) were identified using phenotypic tests. The antifungal susceptibility to fluconazole and voriconazole was determined according to the epidemiological cut-off values of CLSI document M44-A2. Results: Two hundred thirty-two (232) samples were analyzed. The frequency of Candida spp. (other than C. albicans) was 19.82 % (46/232) and C. albicans was 11.20 % (26/232). Candida spp. (other than C. albicans) were the following: C. tropicalis (67.39 %, 31/46), C. glabrata (17.39 %, 8/46), C. parapsilosis (10.86 %, 5/46) and C. krusei (4.34 %, 2/46). Patients from whom Candida spp. (other than C. albicans) were isolated were mostly females (56.52 %), had a history of antimicrobial drugs consumption (67.39 %) and were 60 years of age and older (36.95 %). Most microorganisms were isolated from urine samples (45.65 %). Regarding the antifungal susceptibility of Candida spp. (other than C. albicans), 19.56 % and 21.73 % were resistant to fluconazole and voriconazole, respectively. Conclusions: The high incidence and prevalence of Candida spp. (other than C. albicans) in patients admitted to critical care units of a third-level hospital in Chiclayo, together with resistance to fluconazole and voriconazole, are significant in the morbidity and mortality of these patients.